Correlates of type-2 diabetes mellitus in urban slums population Moradabad - Bahal, Shiv Prasad; Saxena, Sumit; Srivastava, Anurag (International Journal Of Community Medicine And Public Health, 2018)
Background: Epidemiological transitions in India in the 21st century have led to non-communicable diseases becoming a major public health problem of growing magnitude. One of the important diseases in this respect is diabetes, which is considered a “disease of urbanization”. Risk factors for type 2 diabetes mellitus are: age, gender, ethnicity, family history, obesity, inactivity, gestational diabetes, hypertension, cardiovascular diseases, high blood glucose on previous testing, impaired glucose tolerance and glycated hemoglobin ≥5.7%. Methods: A community based cross- sectional study was conducted in urban slums which are the field practice area of Community Medicine department under the head of Teerthanker Mahaveer Medical College and Research Center, Moradabad. The final analysis was conducted on 640 participants. Each interview began with a general discussion to build rapport with the participants. Repeat visit was made on the consecutive day early in the morning to measure fasting blood glucose level with the help of Glucometer. Results: The overall prevalence of diabetes mellitus in the present study was found to be 15.6%. Maximum prevalence of diabetes mellitus was found between the age group of 60-69 years i.e. 44 (28.0%) followed by 26 (19.6%) in 50-59 years and 22 (18.1%) in 40-49 age group. In socioeconomic status, the prevalence of diabetes mellitus was 18 (21.6%) and 26 (25.2%) in class I and class II respectively. Conclusions: Based on study findings it has been observed that there was statistically significant association between socio-demographic variables like age, sex, education, socioeconomic status and type 2 diabetes mellitus.